2019
DOI: 10.1186/s12888-019-2356-4
|View full text |Cite
|
Sign up to set email alerts
|

Mental health status compared among rural-to-urban migrant, urban and rural school-age children in Guangdong Province, China

Abstract: BackgroundPrevious research has documented mental health status among rural-to-urban migrant children (labeled as “migrant children” henceforth) and urban children. However, the findings remain unclear. In addition, far less attention has been paid to rural children’s psychological outcomes. The purpose of this study was to compare mental health status among migrant, urban and rural school-age children in Guangdong Province, China.MethodsThis was a cross-sectional study involving 372 migrant, 254 urban and 268… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 22 publications
5
10
0
Order By: Relevance
“…This correlates with a Swedish study that reported that high school students living away from home experience poor mental health [ 51 ]. Furthermore, we found that high school students living in urban areas have lower instances of self-reported mental health problems than their counterparts who do not live in urban areas, which is consistent with previous studies [ 23 , 52 ]. One possible explanation is that nonurban students have less access to numerous medical resources and are therefore unable to receive psychological support from health-care institutions when they have mental health problems [ 23 , 52 , 53 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This correlates with a Swedish study that reported that high school students living away from home experience poor mental health [ 51 ]. Furthermore, we found that high school students living in urban areas have lower instances of self-reported mental health problems than their counterparts who do not live in urban areas, which is consistent with previous studies [ 23 , 52 ]. One possible explanation is that nonurban students have less access to numerous medical resources and are therefore unable to receive psychological support from health-care institutions when they have mental health problems [ 23 , 52 , 53 ].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, we found that high school students living in urban areas have lower instances of self-reported mental health problems than their counterparts who do not live in urban areas, which is consistent with previous studies [ 23 , 52 ]. One possible explanation is that nonurban students have less access to numerous medical resources and are therefore unable to receive psychological support from health-care institutions when they have mental health problems [ 23 , 52 , 53 ]. Additionally, students living under the care of a single parent tend to be less proactive in health-seeking behavior and face a higher prevalence of mental health problems [ 54 ].…”
Section: Discussionsupporting
confidence: 92%
“…The increasing of urban growth in uence adolescents' emotional and behavioural problems in urban and rural settings(Idris et al, 2019). Study analysis through multiple linear regression found an association between socio demography and mental health among children(Chen et al, 2019). The current study also revealed the same on parental and teacher SDQ total scores which are associated with gender, urban-rural settings, and socio-economic status.…”
supporting
confidence: 54%
“…In this way, the lack of exercise and shortening of sleep time need attention, not only in terms of their physical effects on children, but also the mental effects. Furthermore, Chen et al suggested that children living in rural areas and rural-to-urban migrant children had poorer mental health than children in urban areas 24) . Several other studies have reported that indicators of social disadvantage (single-parent families, parents who are unemployed or have low incomes) are associated with poor mental health in children 34 - 36) .…”
Section: Discussionmentioning
confidence: 99%
“…Also, despite improvements in overall mental health 22) , longterm PTSD after a nuclear disaster and mental health problems associated with evacuation and migration have been pointed out 23) . Furthermore, it should be noted that previous studies have reported that the mental health status of children living in rural areas is worse than that of children in urban areas 24,25) .…”
Section: Introductionmentioning
confidence: 97%